Nigerian pharmacists' self-perceived competence and confidence to plan and conduct pharmacy practice research - Abubakar U; Sulaiman SA; Usman MN; Umar MD (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: Recent studies have revealed that pharmacists have interest in conducting research. However, lack of confidence is a major barrier. Objective: This study evaluated pharmacists' self-perceived competence and confidence to plan and conduct health-related research. Method: This cross sectional study was conducted during the 89th Annual National Conference of the Pharmaceutical Society of Nigeria in November 2016. An adapted questionnaire was validated and administered to 200 pharmacist delegates during the conference. Result: Overall, 127 questionnaires were included in the analysis. At least 80% of the pharmacists had previous health-related research experience. Pharmacist's competence and confidence scores were lowest for research skills such as: using software for statistical analysis, choosing and applying appropriate inferential statistical test and method, and outlining detailed statistical plan to be used in data analysis. Highest competence and confidence scores were observed for conception of research idea, literature search and critical appraisal of literature. Pharmacists with previous research experience had higher competence and confidence scores than those with no previous research experience (p<0.05). The only predictor of moderate-to-extreme self-competence and confidence was having at least one journal article publication during the last 5 years. Conclusion: Nigerian pharmacists indicated interest to participate in health-related research. However, self-competence and confidence to plan and conduct research were low. This was particularly so for skills related to statistical analysis. Training programs and building of Pharmacy Practice Research Network are recommended to enhance pharmacist's research capacity.